Assessment of Maternal Risk Factors in Preterm Labor in A Tertiary Care Hospital of Pakistan: Assessment of Maternal Risk Factors in Preterm Labor - Rahman, Arfa; Yasmin, Tahira; Anjum, Safoora; Hafeez, Sarah; Khurshid, Sadaf; Asif, Sanum (Pakistan Journal of Health Sciences, 2026)
Preterm labor remains a major contributor to perinatal morbidity and mortality, particularly in low- and middle-income countries. Identification of maternal risk factors is essential for prevention, timely intervention, and improved pregnancy outcomes. Objectives: To determine the frequency of maternal risk factors associated with preterm labor in a tertiary care setting. Methods: A descriptive cross-sectional study was conducted at the Department of Obstetrics and Gynaecology, University of Lahore Teaching Hospital, from May 3, 2025, to August 2, 2025. A total of 155 multigravida women aged 20–40 years with gestational age <37 weeks, diagnosed with preterm labor, were included through non-probability consecutive sampling. Data were collected using a structured proforma and analyzed in SPSS version 25.0. Descriptive statistics were calculated, and stratification was done with the chi-square test, considering p≤0.05 as significant. Results: The mean maternal age was 31.03 ± 5.89 years, and mean gestational age at delivery was 33.88 ± 1.43 weeks. The most frequent maternal risk factors were vaginal discharge (46.5%), urinary tract infection (45.2%), anemia in pregnancy (39.4%), previous cesarean section (23.9%), and gestational hypertension (18.1%). A history of previous preterm birth was present in 12.9% of women, leaking per vagina in 11.6%, and placental abruption in 2.6%. Conclusions: Infections, particularly vaginal discharge and urinary tract infection, were the leading maternal risk factors associated with preterm labor in this population. Routine screening and prompt management of maternal infections, alongside targeted antenatal interventions, may help reduce the burden of preterm births.